Antiretroviral therapy potentiates high-fat diet induced obesity and glucose intolerance - Mark E. Pepin; Lindsey E. Padgett; Ruth E. McDowell; Ashley R. Burg; Manoja K. Brahma; Cassie Holleman; Teayoun Kim; David Crossman; Olaf Kutsch; Hubert M. Tse; Adam R. Wende; Kirk M. Habegger (Elsevier, 2018)
Objective: Breakthroughs in HIV treatment, especially combination antiretroviral therapy (ART), have massively reduced AIDS-associated mortality. However, ART administration amplifies the risk of non-AIDS defining illnesses including obesity, diabetes, and cardiovascular disease, collectively known as metabolic syndrome. Initial reports suggest that ART-associated risk of metabolic syndrome correlates with socioeconomic status, a multifaceted finding that encompasses income, race, education, and diet. Therefore, determination of causal relationships is extremely challenging due to the complex interplay between viral infection, ART, and the many environmental factors. Methods: In the current study, we employed a mouse model to specifically examine interactions between ART and diet that impacts energy balance and glucose metabolism. Previous studies have shown that high-fat feeding induces persistent low-grade systemic and adipose tissue inflammation contributing to insulin resistance and metabolic dysregulation via adipose-infiltrating macrophages. Studies herein test the hypothesis that ART potentiates the inflammatory effects of a high-fat diet (HFD). C57Bl/6J mice on a HFD or standard chow containing ART or vehicle, were subjected to functional metabolic testing, RNA-sequencing of epididymal white adipose tissue (eWAT), and array-based kinomic analysis of eWAT-infiltrating macrophages. Results: ART-treated mice on a HFD displayed increased fat mass accumulation, impaired glucose tolerance, and potentiated insulin resistance. Gene set enrichment and kinomic array analyses revealed a pro-inflammatory transcriptional signature depicting granulocyte migration and activation. Conclusion: The current study reveals a HFD-ART interaction that increases inflammatory transcriptional pathways and impairs glucose metabolism, energy balance, and metabolic dysfunction. Keywords: Antiretroviral therapy, Obesity, Glucose intolerance, Adipose tissue inflammation, Insulin resistance, Macrophage activation